The Lebanese-Israeli maritime agreement: A conflict resolution model or a geopolitical stopgap? - Ismail, A. (Pólusok Folyóirat, 2025)
The 2022 US-mediated maritime delimitation agreement between Lebanon and Israel marked a significant technical achievement, resolving an 860 km² overlap in the Exclusive Economic Zone (EEZ) and enabling future offshore gas exploration. This article examines the domestic political and economic factors in Lebanon and Israel that facilitated the settlement. It assesses the roles of external actors, particularly the United States, the EU, and the UNIFIL, in shaping and supporting the agreement. Drawing on conflict resolution theory, including models of ripeness, interest-based negotiation, conflict management and transformation, the analysis reconstructs the negotiation process and examines the implementation obstacles. It argues that, although the agreement represents a successful technical compromise, persistent domestic gridlock in Lebanon, limited enforcement mechanisms, and investor hesitation have delayed drilling and reinforced Israel’s asymmetric benefits. The absence of multilateral frameworks or maritime security protocols further limits the agreement’s potential as a model for broader cooperation in the Eastern Mediterranean. The article concludes that durable peace and stability will require accelerated Lebanese energy development, institutionalized EEZ coordination and formal maritime security arrangements.